FAKTOR-FAKTOR KEBERHASILAN PENGELOLAAN KOPERASI SEKOLAH - -, Hanafi (Jurnal Mahasiswa Prodi SI Manajemen, 2013)
The purpose of the research to find thesuccsess factors of cooperation schoolmanage. The sampel is all of cooperationmember, that is teachers and employerSMPN 2 Rambah and all of family consist of79 persons. To analysis the data by quisionerand the result of study library.From the result of the research thereare several factors to find the success ofcooperation: management handling ofcooperation, financial capital of cooperation,and financial account of cooperation.From the regresi linear analysis testingusing SPSS we get similarity:Y = 6,330 + 0,444 (X1) + 0,376 (X2) + 0,133(X3) + 0,243 (X4).The last suggestion for the element ofcooperation:1. Increase the quality of worker to makecooperation success.2. All element cooperation members candevelop, manage the cooperationsejahtera SMPN 2.For the headmaster as a leader ofcooperation please always give spirit andsuggestion to increase the cooperationSejahtera SMPN 2 Rambah